DAMPAK PENGUMUMAN BOND RATING TERHADAP RETURN SAHAM DAN VOLUME PERDAGANGAN SAHAM PERUSAHAAN YANG TERDAFTAR DI BURSA EFEK INDONESIA - Desi Elysa Saraswati; Magdalena Nany; Lyna Lyna (Universitas Slamet Riyadi, 2021)
A bond rating is a rating that independent agencies issue to measure the credit quality of a particular bond. The bond rating measures the financial strength of the company issuing the bond, and its ability to make interest payments and repay the principal of the bond, when due. The objective of this research was to give empirical evidence about the effects of stock return and stock trading volume on bond rating announcements partially. The objective of this research was also to give empirical evidence about the differences between stock return and stock trading volume before and after bond rating announcements. This research examined 59 stock issuer on Indonesia Stock Exchange which announced bond rating during period 2015-2017. Data were analyzed by paired sample t-test and simple regression analysis. The results show that there are no differences between stock return and stock trading volume before and after bond rating announcements. The results also show that bond rating announcements does not efect both stock return and stock trading volume partially.